Security Enhanced EMV-Based Mobile Payment Protocol - Ming-Hour Yang (The Scientific World Journal)
Near field communication has enabled customers to put their credit cards into a smartphone and use the phone for credit card transaction. But EMV contactless payment allows unauthorized readers to access credit cards. Besides, in offline transaction, a merchant’s reader cannot verify whether a card has been revoked. Therefore, we propose an EMV-compatible payment protocol to mitigate the transaction risk. And our modifications to the EMV standard are transparent to merchants and users. We also encrypt the communications between a card and a reader to prevent eavesdropping on sensitive data. The protocol is able to resist impersonation attacks and to avoid the security threats in EMV. In offline transactions, our scheme requires a user to apply for a temporary offline certificate in advance. With the certificate, banks no longer need to lower customer’s credits for risk control, and users can have online-equivalent credits in offline transactions.